CHANGES IN COPPER METABOLISM UNDER THE INFLUENCE OF HELMINTHS - Alimova Ozoda Bekmurodovna (Лучшие интеллектуальные исследования, 2024)
Abstract: The article provides information about the changes in copper metabolism that occur under the influence of helminths and their consequences.